Risk factors in outsourced software development: A systematic literature review - Teh, Piak San; Abd Wahab, Alawiyah (2016)
Software development outsourcing has recently become part of organizations’ overall business strategy to gain global competitiveness. However, it is widely recognized that outsourcing project involves risks and sometimes leads to undesirable consequences.Previous researchers have identified several risks in the software development outsourcing that could cause the project abandonment such as lack of communication and technical skills.The aim of this paper is to examine the literature on outsourced software development in order to identify some risks that could occur during the pre-contract, contract and post-contract phase of the outsourcing life cycle. It is anticipated that by understanding these risks, project managers could better manage them and subsequently increase the possibility of the success of outsourcing project.The findings show that 18 out of 41 studies were concerned with outsourcing software development risk factors.The 15 risk factors found were mapped onto the three phases of the outsourcing life cycle.The most identified risk factors (61%) was lack of required technical skills and competencies.